ANALYSIS OF THE PRABOWO–GIBRAN CABINET’S COMMUNICATION STRATEGY FROM THE PERSPECTIVE OF FREDERICK TAYLOR’S AND MAX WEBER’S CLASSICAL THEORIES - Regina Sesilia br Ginting; Rifa Aulia Putri; Vyola Greacesya Nasution; Wanda Marhamah Daulay; Feni Khairifah (OPINI: Journal of Communication and Social Science, 2025)
This study examines the communication strategies implemented by the Prabowo–Gibran Cabinet following their inauguration in 2024, using a qualitative approach and theoretical analysis grounded in classical management principles: Frederick Taylor’s Scientific Management and Max Weber’s Bureaucratic Theory. Data were collected from official documents produced by ministerial communication staff, political journalists, public policy analysts, discourse analysis of official speeches, as well as documentary studies and observational studies of the cabinet’s public communication policies and media coverage both mass media and social media between October 2024 and September 2025. The key findings indicate that: (1) the cabinet combines personal image strategies (leader branding) with managerial techniques emphasizing efficiency and organizational discipline; (2) the use of social media and symbolic performances (military-style retreats, uniformed appearances) functions as a tool for constructing narratives of legitimacy; (3) internal communication structures are strongly shaped by Weberian bureaucratic logic yet infused with Taylorian principles through the emphasis on operational standards and performance measurement of public communication campaigns; and (4) tensions between the demands of bureaucratic control and the need for flexible public communication create potential narrative dissonance that requires careful management.